Lobular capillary hemangioma of the nasal cavity treated by radiofrequency excision: a retrospective study - Garag, Santosh; Jalisatgi, Roshan R.; Jinka Satyanarayan, Arunkumar; Naik, Ashok S.; Shetty, Sushan (International Journal of Otorhinolaryngology and Head and Neck Surgery, 2019)
Background: The objective of the study was to assess the clinical presentation, radiological features and treatment by radiofrequency excision of lobular capillary hemangioma of the nasal cavity in a tertiary care hospital. Methods: A retrospective descriptive study of capillary hemangioma of the nasal cavity on patients attending a tertiary care hospital from January 2015 to January 2019 was conducted. Case records were analysed and results were tabulated. Results: There were 14 patients of capillary hemangioma of the nasal cavity of which 11 were males and 3 females with age ranging from 15 to 68 years. Epistaxis was the most common symptom followed by nasal obstruction. Anterior nasal septum was the most commonly affected area followed by posterior nasal septum, nasal vestibule and inferior turbinate. CT scans showed enhancing lesion with no bony erosion. Patients underwent endoscopic and classical excision by radiofrequency. No patient had any recurrence over 6 to 24 months follow-up. Conclusions: Lobular capillary hemangiomas of the nasal cavity present with epistaxis as the common symptom and occur most commonly over anterior part of nasal septum. Excision by radiofrequency results in minimal complications without any recurrence.